2017
DOI: 10.1016/j.pharep.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of histamine in the regulation of the viability, proliferation and transforming growth factor β1 secretion of rat wound fibroblasts

Abstract: The regulatory influence of histamine on wound fibroblast function (viability/metabolic activity or secretion of TGFβ1) is dependent on H1 receptor stimulation. Contrary to wound fibroblasts, these cells express a very low level of H1 receptors when isolated from intact dermis and histamine is unable to modify their metabolic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…Our previous study has shown that MC-derived histamine regulates TGF-β1 1 , but our current study also demonstrates a link between H1HR and TGF-β1. To support our findings, during would healing, histamine increased TGF-β1 in fibroblasts, which was blocked by pre-treatment with an H1HR inhibitor 42 . Our studies found that increased biliary TGF-β1 was induced by histamine treatment both in vitro and in vivo and since cholangiocytes express HDC and secrete histamine 22 , we suspect that histamine treatment in DKO mice may regulate biliary TGF-β1 via H1HR/PKC-α signaling since TGF-β1 activation was reduced with H1HR inhibition.…”
Section: Discussionsupporting
confidence: 85%
“…Our previous study has shown that MC-derived histamine regulates TGF-β1 1 , but our current study also demonstrates a link between H1HR and TGF-β1. To support our findings, during would healing, histamine increased TGF-β1 in fibroblasts, which was blocked by pre-treatment with an H1HR inhibitor 42 . Our studies found that increased biliary TGF-β1 was induced by histamine treatment both in vitro and in vivo and since cholangiocytes express HDC and secrete histamine 22 , we suspect that histamine treatment in DKO mice may regulate biliary TGF-β1 via H1HR/PKC-α signaling since TGF-β1 activation was reduced with H1HR inhibition.…”
Section: Discussionsupporting
confidence: 85%
“…These findings suggest that histamine targeting has pharmacological potential. In addition, histamine participates in the wound-healing process by increasing the viability of rat wound fibroblasts and promoting the production of TGF- β in an H1R-dependent manner [ 63 ].…”
Section: Regulatory and Immunomodulatory Functions Of Histaminementioning
confidence: 99%
“…Our earlier experiments performed on cells isolated from wound models confirmed that histamine accelerates the metabolism of the cells and increases TGFβ1 secretion [12]. This effect was not seen in cultures of naïve fibroblasts derived from the intact skin of rats [12]. Some other studies have shown that histamine may modulate collagen synthesis in human dermal fibroblast cultures [13] or in skin fibroblasts derived from guinea pigs [14].…”
Section: Introductionmentioning
confidence: 83%
“…Secondly, histamine may increase collagen synthesis by exerting a direct influence on the granulation tissue cells responsible for the synthesis of the extracellular matrix. Our earlier experiments performed on cells isolated from wound models confirmed that histamine accelerates the metabolism of the cells and increases TGFβ1 secretion [12]. This effect was not seen in cultures of naïve fibroblasts derived from the intact skin of rats [12].…”
Section: Introductionmentioning
confidence: 89%